The production and consumption of land use planning: A neo-institutional economic perspective & three Taiwan case studies of planning layering. (December 2020) - Lai, Lawrence W.C.; Davies, Stephen N.G.; Chan, Edwin H.W.; Chua, Mark Hansley; Lin, C.L.
Highlights: First account of layout planning (platting) as a production process. A public good account of layout planning (platting). A systematic neo-institutional economic inquiry of physical planning. Abstract: Hitherto research by planning researchers on the economics of land use planning have sought to interpret and re-interpret the role of such planning as a non-market measure to: (a) remedy market failure; (b) delineate and re-delineate property rights to land; and (c) determine the economic impact (effectiveness) of (a) and (b) on, say, efficiency (welfare), property values, and development. This paper develops the thesis from a neo-institutional economic perspective that the land use planning process is not just an indicative exercise of plan preparation, promulgation, and interpretation, but also a real production and consumption process . The former for laying out or platting a greenfield site is explained by elaborating on the analogy of cutting a diamond, while the latter is explained in terms of the physical features of public goods other than being informational. It then proceeds to how a formal de jure layout imposed by the state as a kind of corrective for an antecedent bottom-up (and in this sense "spontaneous") de facto pre-existing layout constrains subsequent development of a place. Three Taiwanese examples are used to show how pre-existing 'cuts', to places that varied in terms of population and modernity, may constrain and survive subsequent cuts that seek to modernize and reform the former. Reasons based on transaction costs are offered for the key observations.